Oral and masticatory rehabilitation using osseointegrated dental implants after resective treatment of multicystic ameloblastoma in the lower jaw with a fibula graft - João Ricardo Almeida Grossi; Tatiana Miranda Deliberador; Tielly Saad; Rafaela Scariot; Joao Cesar Zielak; Allan Fernando Giovanini (Wolters Kluwer Medknow Publications, 2018)
Ameloblastoma is an aggressive odontogenic tumor which typically occurs between third and fourth decade of life that often needs resective approach. Immediate reconstruction may show better results. The treatment of multicystic ameloblastoma in the mandible being a rare case that occurred in the late second decade of life, which was surgically removed along with the affected teeth with safety margins, and the region was immediately reconstructed using a vascularized graft, removed from the fibula. Its integration, in combination with osseointegrated dental implants and fixed implant-supported prostheses, restored chewing function and esthetics. After 6 years from fibular graft and 24 months of dental implants, an excellent outcome was observed, with oral health and normal functions properly restored, and the immediate reconstruction of the mandible in resective cases, associated with oral rehabilitation with dental implants, may be considered a suitable treatment option.